Cognitive multi-agent systems : structures, strategies and applications to mobile robotics and robosoccer /: structures, strategies and applications to mobile robotics and robosoccer. ([2019]) - Hajduk, Mikuláš; Sukop, Marek; Haun, Matthias
No abstract available